PENGENDALIAN PENGELOLAAN KAS TERHADAP LIKUIDITAS PERUSAHAAN (STUDI KASUS CV. THREE COOMUNIKA SURABAYA) - ANGGI NOVA, GRANESTYA Anggi (Jurnal Akuntansi AKUNESA, 2013)
To find out whether cash management control of CV. Three Coomunika Surabaya could ensurethe liquidity of the company, data that used in this study a primary data, that we got throughresearch on the area, data, observations, and interviews with corporate leader of the company.The reason of the unliquidity of CV. Three Coomunika, because there was no monitoring of cashmanagement and not good structure of the organization which affect to under performance of thecompany and employee’s salary delay.Keyword : Operation, Management, Cash and Likuiditas